2013
DOI: 10.3390/ijerph10094454
|View full text |Cite
|
Sign up to set email alerts
|

Lung Deposition Analyses of Inhaled Toxic Aerosols in Conventional and Less Harmful Cigarette Smoke: A Review

Abstract: Inhaled toxic aerosols of conventional cigarette smoke may impact not only the health of smokers, but also those exposed to second-stream smoke, especially children. Thus, less harmful cigarettes (LHCs), also called potential reduced exposure products (PREPs), or modified risk tobacco products (MRTP) have been designed by tobacco manufacturers to focus on the reduction of the concentration of carcinogenic components and toxicants in tobacco. However, some studies have pointed out that the new cigarette product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 128 publications
(283 reference statements)
0
37
0
1
Order By: Relevance
“…58,105,107 To date, there is insufficient evidence to support the notion that exposure to exhaled aerosol has a deleterious impact on bystanders. 26 Some studies have found very low concentrations of air pollutants across different types, liquids, puff durations, and nicotine concentrations.…”
Section: Inclusion Of E-cigarettes In Smoke-free Air Lawsmentioning
confidence: 99%
“…58,105,107 To date, there is insufficient evidence to support the notion that exposure to exhaled aerosol has a deleterious impact on bystanders. 26 Some studies have found very low concentrations of air pollutants across different types, liquids, puff durations, and nicotine concentrations.…”
Section: Inclusion Of E-cigarettes In Smoke-free Air Lawsmentioning
confidence: 99%
“…Parameters of E-Cig emission, such as aerosol size, mass output, and chemical composition, vary by device and e-liquid types and are predicted to impact the user's exposure to the E-Cig aerosol. For example, aerosol size strongly affects how much of an aerosol is delivered to different regions of the lung and how much is retained in the oral cavity (16,82).…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%
“…Currently, in silico studies addressed to respiratory lung modeling have been covering detailed patient-specific 3D lung reconstruction [13,14], nasopharynx-trachea ventilation features [6,7,15], 3D-1D coupling of upper and middle airway segments, and FSI simulations [16]. The lumped models operate with lung mechanics in terms of tidal volume and pressure with lower details [17,18].…”
Section: Discussionmentioning
confidence: 99%